Toward a resilient complex adaptive system view of business models. Issue 3 (June 2021) - Liu, Jucun; Tong, Tony W.; Sinfield, Joseph V.
Abstract: This paper employs the theory of resilient complex adaptive systems (RCAS) to offer a versatile and universal foundation for the concept of a business model that facilitates connections between prior works while enabling future exploration with a common language. The proposed business model construct is developed by first exploring the field of systems to highlight how the concept of an RCAS can be employed to provide a more robust conceptualization of a business model than previous constructs. A thematic analysis of the literature is then conducted to translate the fundamental requirements of an RCAS into the business model context. This system view is inherently abstraction tolerant and provides a foundation for both academic research and practical applications. Specifically, it addresses two key gaps in the business model literature. First, the comprehensive nature of the system model naturally calls out important aspects of business models that have been largely ignored in the literature. Second, the construct provides a comprehensive means to connect the work of business model scholars and practitioners outlined in more than 150 studied articles, highlighting how each earlier research effort has employed a construct that is actually part of a grander whole.